Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Jasa Transportasi Online Maxim di Kota Palembang - Ruwananda, M.Edwin; Nailis, Welly (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of Service Quality on Customer Satisfaction of online transportation services in Palemang City. The research method used is a quantitative method with a type of comparative causal research. The data used in the study are primary and secondary data. The sampling technique uses puruposive sampling technique. This study used a sample of 100 respondents who were people living in Palembang City. The data analysis used is by F test, T test, and multiple linear analysis. The results of test F show that the variable of service quality simultaneously affects the satisfaction of Maxim customers in Palembang City.